2022
DOI: 10.1145/3549481
|View full text |Cite
|
Sign up to set email alerts
|

"A Time and Phase for Everything" - Towards A Self Regulated Learning Perspective on Computational Support for Esports

Abstract: Computational support for learning in the domain of esports has seen a great deal of attention in recent years as an effective means of helping players learn and reap the benefits of play. However, previous work has not examined the tools from a learning theory perspective to assess if learning is prompted and supported in the right place and time. As a first step towards addressing this gap, this paper presents the results of two studies: a review of existing computational tools, and an online survey of espor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…It was hypothesized that this could be attributed to the design of LoL, as the game itself records players’ progress and provides information, potentially reducing the need for extensive monitoring or self-reflection among LoL players. Furthermore, Kleinman et al (2022) proposed that digital tools may offer valuable support for e’athletes in implementing their self-regulatory skills. Previous research has shown that psychological skills training (PST) interventions improved athletes’ self-regulatory processes and lead to stressful situations being appraised as a challenge rather than a threat ( Hogue, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…It was hypothesized that this could be attributed to the design of LoL, as the game itself records players’ progress and provides information, potentially reducing the need for extensive monitoring or self-reflection among LoL players. Furthermore, Kleinman et al (2022) proposed that digital tools may offer valuable support for e’athletes in implementing their self-regulatory skills. Previous research has shown that psychological skills training (PST) interventions improved athletes’ self-regulatory processes and lead to stressful situations being appraised as a challenge rather than a threat ( Hogue, 2020 ).…”
Section: Introductionmentioning
confidence: 99%